Curriculum Transformation and Islamic Intellectual Identity in the Era of Globalization: Evidence from Indonesia - Firiyanto; Fajri Ismail; Indah Wigati; Yuniar (Sustainable, 2026)
Globalization has brought significant changes to education systems worldwide. Islamic education faces the challenge of adapting to developments in science, technology, and global social dynamics while maintaining its intellectual identity. This study aims to analyze the challenges faced by Islamic education in the era of globalization, examine institutional responses, and identify curriculum transformation strategies in Indonesia. This research employs a qualitative approach using a literature review method, examining academic sources published between 2020 and 2025. Data were analyzed using descriptive and thematic analysis. This study contributes by proposing an integrative framework that balances curriculum transformation, digital literacy, institutional governance, and Islamic intellectual identity preservation. The findings indicate that globalization encourages curriculum transformation through the integration of religious and general sciences, digital literacy strengthening, and adaptive learning models. However, challenges include the potential knowledge dichotomy, limited digital infrastructure, and the risk of weakening Islamic intellectual identity. Theoretical implications suggest that Islamic education requires strong epistemological foundations rooted in Islamic values to avoid marginalization of traditional scholarship. Practical implications indicate that educational institutions need comprehensive strategies integrating technological innovation with value preservation. Limitations: This study is limited to literature published between 2020 and 2025 within the Indonesian context. Future research should conduct empirical studies across diverse institutional contexts. An integrative approach balancing innovation, technology, and Islamic values is necessary to ensure Islamic education remains relevant and competitive globally.